Existence and uniqueness of nonlinear Goursat problem in the class of Denjoy?Carleman - Latreche S.; Guerbati K.; Guefaifia R.; Mekawy I.; Alharbi A.; Jan R. (Elsevier B.V., 2025)
The problem of existence and uniqueness of nonlinear Goursat is studied by Claude Wagschal in different spaces: holomorphic spaces, partially holomorphic, continuous-Gevrey and Gevrey-holomorphic. In this paper, we replace the sequence (n!)d?1 in the case Gevery with suitable sequence (Mn) in the case Carleman. After that, we study the problem of existence and uniqueness of nonlinear Goursat problem in Denjoy?Carleman space. ? 2024 The Author(s)